2015
DOI: 10.1038/ejhg.2015.105
|View full text |Cite
|
Sign up to set email alerts
|

A systematic variant screening in familial cases of congenital heart defects demonstrates the usefulness of molecular genetics in this field

Abstract: The etiology of congenital heart defect (CHD) combines environmental and genetic factors. So far, there were studies reporting on the screening of a single gene on unselected CHD or on familial cases selected for specific CHD types. Our goal was to systematically screen a proband of familial cases of CHD on a set of genetic tests to evaluate the prevalence of disease-causing variant identification. A systematic screening of GATA4, NKX2-5, ZIC3 and Multiplex ligation-dependent probe amplification (MLPA) P311 Ki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
18
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 23 publications
5
18
0
1
Order By: Relevance
“…In this regard, the absence of this variant in the public and in‐house databases, high pathogenicity predicted by the four in silico analyses, and gene information by OMIM and UCSC survey (Table S1), in conjunction with the previous description of the same variant in a French family with ASD2,12 indicate that this variant is responsible for the development of ASD2 in this Japanese family. According to the ACMG Standards and Guidelines,13 this variant is regarded as a “likely pathogenic variant,” because this variant is positive for PS1 (same amino acid change as an established pathogenic variant), PM2 (absent from controls), PP1 (co‐segregation with disease phenotype in multiple affected family members), and PP3 (multiple lines of computational evidence in support of a deleterious effect).…”
Section: Discussionmentioning
confidence: 65%
See 3 more Smart Citations
“…In this regard, the absence of this variant in the public and in‐house databases, high pathogenicity predicted by the four in silico analyses, and gene information by OMIM and UCSC survey (Table S1), in conjunction with the previous description of the same variant in a French family with ASD2,12 indicate that this variant is responsible for the development of ASD2 in this Japanese family. According to the ACMG Standards and Guidelines,13 this variant is regarded as a “likely pathogenic variant,” because this variant is positive for PS1 (same amino acid change as an established pathogenic variant), PM2 (absent from controls), PP1 (co‐segregation with disease phenotype in multiple affected family members), and PP3 (multiple lines of computational evidence in support of a deleterious effect).…”
Section: Discussionmentioning
confidence: 65%
“…Previous studies have also revealed various GATA4 variants in familial forms of ASD2 with and without PS 5, 12. Thus, it is likely that GATA4 variants frequently cause ASD with and without PS and occasionally lead to other types of CHDs, depending on the effects of other multiple genetic and environmental factors.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…12 Altogether, de novo CNV and point mutations could account for as much as ≈20% of CHD. This percentage is impressive, but what is even more notable is the fact that these discoveries concern essentially so-called sporadic CHD cases that represent the bottom of the iceberg because familial cases are estimated to account for only 4% to 9% of CHDs.…”
Section: Bouvagnetmentioning
confidence: 99%